Familial Congenital Digital Clubbing - Report of Two Siblings - Das, Dillip Kumar; Shukla, Suprabha (Indian Journal of Child Health, 2014)
Digital clubbing can be a striking physical finding. Etiology of clubbing in most of the time is secondary to somesystemic illness. Familial clubbing is a rare occurrence and incidence or prevalence of such occurrence is notknown. We are presenting two cases (brother and sister) with digital clubbing in all the four limbs. Systemicexamination and laboratory investigation were normal. Parents were assured about the benign nature of the disease and the children were kept under regular follow up.